PEMANFAATAN MEDIA TIK SIMULASI SEBAGAI SUBSTITUTE EKSPERIMEN PADA PEMBELAJARAN ALAT UKUR DI SMP - Novita Asma Ilahi; Agus Suyatna; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2014)
The purpose of this study are: to determine an increase in cognitive learning outcomes, to grow the students science process skills, to form students character, to improve students activities, and to grow positive attitudes of students after they use of simulation ICT media as a substitute experiments on learning measuring instruments. The research was conducted in the first semester of the academic year 2013/2014 in junior high school Muhammadiyah Pringsewu. The research used purposive sampling technique, select one class from all over the existing class VII. Sample of research was 25 students of class VII 1. The research design is used an One-Shot Case Study. Based on the results of a study using simulation ICT media as a substitute experiments on measuring instruments learning increased cognitive learning outcomes of students, can grow science process skill of students, form the character of students, to improve students activities, and to grow a positive attitude of students.Penelitian ini bertujuan untuk: mengetahui peningkatan hasil belajar ranah kognitif, menumbuhkan KPS, membentuk karakter, mengembangkan aktivitas, dan menumbuhkan sikap positif siswa setelah pemanfaatan media TIK simulasi sebagai substitute eksperimen pada pembelajaran alat ukur. Penelitian dilaksanakan pada semester ganjil tahun ajaran 2013/2014 di SMP Muhammadiyah Pringsewu, Kabupaten Pringsewu. Penelitian menggunakan teknik purposive sampling, sehingga dipilih satu kelas dari seluruh kelas VII yang ada. Sampel penelitian berjumlah 25 siswa dari kelas VII 1. Berdasarkan hasil penelitian memanfaatkan media TIK simulasi sebagai substitute eksperimen pada pembelajaran alat ukur diketahui terdapat peningkatan hasil belajar ranah kognitif siswa, dapat menumbuhkan KPS siswa, dapat membentuk karakter siswa, dapat mengembangkan aktivitas siswa, dan dapat menumbuhkan sikap positif siswa.Kata kunci: aktivitas, karakter, keterampilan proses sains, media TIK simulasi, substitute eksperimen